Facility Location Planning in Relief Logistics: Decision Support for German Authorities - Diehlmann, Florian (Produktion und Energie, 2022)
The delivery of essential goods to beneficiaries in the aftermath of a disaster is one of the main objectives of relief logistics. Thereby, the present work aims to improve relief logistics by improving the location selection of warehouses, distribution centers, and points of distribution. Consequently, it offers the potential to significantly improve the distribution of goods in the aftermath of future disasters and, thereby, increase disaster resilience.